Handbook of plant disease identification and management - Aglave, Balaji (Boca Raton, Florida : CRC Press, 2019)
Handbook of Plant Disease Identification and Management presents the fundamentals of plant diseases identification based on symptomology and management focusing mainly on integrated pest management approach. It discusses a variety of techniques for the diagnosis of crop disease, losses due to crop diseases, and theories behind disease management. It describes how society is constraining the possibilities for management of crop diseases by changing the environment; biologically controlling crop diseases; and the epidemiologic and genetic concepts of managing host genes. This book discusses managing diseases through diverse chemical, biological, and physical methods. It highlights climatic factors affecting crops by creating favorable condition for most of the diseases. This book serves as a complete guide for growers, researchers, and graduate students to understand basics of plant disease identification. It explains the disease cycle for respective crops with favorable conditions promoting disease development. It intends to aid growers in managing diseases and help scientists with future research.
OCLC-licensed vendor bibliographic record.
Keywords: Plant diseases -- Handbooks, manuals, etc; Phytopathogenic microorganisms -- Control; TECHNOLOGY & ENGINEERING / Agriculture / General; SCIENCE / Life Sciences / Botany; TECHNOLOGY / Agriculture / General